ANALISIS FAKTOR FAKTOR LAYANAN PAJAK TERHADAP WAJIB PAJAK ORANG PRIBADI DI KPP BATAM SELATAN - Kaprilianto, Okta; Siregar, Dian Lestari (SCIENTIA JOURNAL, 2021)
E-filing, e-billing and e-spt are part of the online-based tax service system issued by the Directorate General of Taxes as a modernization step in fulfilling tax obligations and to improve taxpayer compliance. The purpose of this study was to analyze how much influence e-filing, e-billing and e-like on the compliance of individual taxpayers in KPP Pratama Batam Selatan. This data collection was carried out by means of a questionnaire measured by a Likert scale. The total respondents of this study were 100 respondents who were calculated using the Slovin formula. The data analysis method used in this research is quantitative data analysis with multiple linear regression analysis techniques. The results of this study indicate that the e-filing and e-spt variables have a significant effect on individual taxpayer compliance at KPP Pratama Batam Selatam. While the e-billing variable does not have a significant effect on individual taxpayer compliance at KPP Pratama Batam Selatan